Ultrathin MXene‐Micropattern‐Based Field‐Effect Transistor for Probing Neural Activity. Issue 17 (29th February 2016) - Xu, Bingzhe; Zhu, Minshen; Zhang, Wencong; Zhen, Xu; Pei, Zengxia; Xue, Qi; Zhi, Chunyi; Shi, Peng
Abstract : A field‐effect transistor (FET) based on ultrathin Ti3 C2 –MXene micropatterns is developed and utilized as a highly sensitive biosensor. The device is produced with the microcontact printing technique, making use of its unique advantages for easy fabrication. Using the MXene–FET device, label‐free probing of small molecules in typical biological environments and fast detection of action potentials in primary neurons is demonstrated.